2022
DOI: 10.4236/fns.2022.1311062
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Fermented Camel Milk Prepared Using Different Microbial Cultures

Abstract: This study investigated the effect of using different combinations of commercial starter culture and lactobacilli strains on the antioxidant properties of fermented camel milk for 14 days. The bacterial strains included Lb. casei subsp. casei B-1922, Lb. paracasei subsp. paracasei B-4560, Lb. rhamnosus B-442 and Lb. rhamnosus B-1445.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Also, Dos Santos et al ( 2017 ) found that the TPC in bio-fermented goat milk has been increased in samples supplemented with grape pomace extract. The differences among treatments in TPC may be due to the proteolytic activity of probiotic strains on milk proteins, which may release bioactive compounds during fermentation and storage such as amino acids with phenolic side chains (Abou-Soliman et al, 2022 ). Also, the increased addition of carob molasses increased the TPC in fermented milk.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Dos Santos et al ( 2017 ) found that the TPC in bio-fermented goat milk has been increased in samples supplemented with grape pomace extract. The differences among treatments in TPC may be due to the proteolytic activity of probiotic strains on milk proteins, which may release bioactive compounds during fermentation and storage such as amino acids with phenolic side chains (Abou-Soliman et al, 2022 ). Also, the increased addition of carob molasses increased the TPC in fermented milk.…”
Section: Resultsmentioning
confidence: 99%